Integration of Functional MRI and White Matter Tractography in CyberKnife Radiosurgery. (December 2017) - Sun, Lu; Qu, Baolin; Wang, Jinyuan; Ju, Zhongjian; Zhang, Zizhong; Cui, Zhiqiang; Jack, Yang; Ling, Zhipei; Yu, Xinguang; Pan, Longsheng
Purpose: To investigate the efficacy of the integration of functional magnetic resonance imaging and diffusion-tensor imaging tractography data into CyberKnife radiosurgery for intracranial tumor management. Materials and Methods: Functional neuroimaging, anatomical magnetic resonance imaging, and computed tomography images of patients with brain lesions in critical areas were acquired before radiosurgery. The acquired data sets were coregistered using the MIM image fusion software module and then were imported into the CyberKnife Robotic Radiosurgery System (Multiplan 4.0.2) for delineating the target, organs at risk, and possible nearby functionally relevant cortical and subcortical areas. Radiation dose distributions with and without the functionally relevant cortical and subcortical areas into the optimization process were developed and compared. Results: There were significant differences between the treatment plans with and without the functionally relevant cortical and subcortical areas into the optimization process. An average 22.71% reduction in the maximum dose to functional areas was observed. No neurological complication due to radiation damage was observed in the follow-up period. Conclusion: The functional neuroimaging could be easily and reliably integrated into the CyberKnife treatment planning. Consideration of functional structures and fiber tracts during treatment planning could clinically reduce the radiation doses to these critical structures, thereby preserving its unique function of brain.